"It Doesn't All Just Stop at 18": Psychological Adjustment and Support Needs of Adults Born with Cleft Lip and/or Palate. (September 2015) - Stock, Nicola Marie; Feragen, Kristin Billaud; Rumsey, Nichola
Background: Cleft in the lip and/or the palate (CL/P) is considered to be a lifelong condition, yet relatively little is known about the long-term outcomes for patients. Existing literature is largely outdated and conflicted, with an almost exclusive focus on medical aspects and deficits. Objective: To explore the psychological adjustment and possible support needs of a large number of adults born with CL/P from their own perspective. Design: Fifty-two individual telephone interviews eliciting qualitative data. Results: Qualitative analysis identified five themes. Participants reported a range of challenges in relation to discharge from the service, additional surgery as an adult, social and romantic relationships, higher education, vocational achievement, and access to psychological support. The findings imply that most adults with a cleft adjust well to these challenges and report many positive outcomes. For a minority of patients, issues attributed to the cleft may continue to cause distress in adulthood. Conclusions: Adults with CL/P may require psychological support, information about the heritability of cleft, signposting and referrals from nonspecialists, support regarding further treatment, and opportunities to take part in research and activities. New issues arising in adulthood, such as entering the workplace, forming long-term relationships, and starting a family, may warrant both further investigation and additional support. Further work is needed to identify the factors that contribute to psychological distress and resilience, as well as the timing of particular points of risk and opportunity for personal growth.